Islamic economic order and responsibilities of Muslim traders: اسلامی نظم معیشت اور مسلم تاجروں کی ذمہ داریاں - Irfan, Dr. Muhammad; Majid , Dr. Abdul; Khan, Shamshir (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Islam is a natural religion that encompasses all aspects of life and presents a complete and comprehensive way of life for humanity. It leaves no aspect of human affairs unaddressed, providing full guidance in every sphere. One of the most important aspects of human life is economic matters. Islam provides complete guidance in economic affairs as well, offering a just economic system in which every individual has access to the necessary economic facilities to live their life. The purpose of writing this research paper is to find out the moral values of the Islamic economic system, which if implemented can provide every individual with adequate economic resources. There is no doubt that if there is inequality in the distribution of wealth, the social life of humanity will be severely impacted by this inequality, leading to the division of society into two groups. One group consists of those who are equipped with all the basic necessities of life and have control over more resources than their share. The other group consists of those who struggle to even afford a basic meal. This occurs when there are no just reforms in the economic system.